The Need For Help Model Can Reduce Anxiety Levels of Losing a Baby in Severe Pre-Eclampsia Pregnant Women - Mufida, Hasna Ayu; Sulastri, S (Jurnal Berita Ilmu Keperawatan, 2022)
The need for help model is expected to be able to handle patient complaints in an emergency situation appropriately and quickly through 4 stages such as identification, assistance, validation, and coordination by applying knowledge, assessment, skills, spiritual and material resources. This model is appropriate to be applied to pregnant women with severe pre-eclampsia in an emergency situation who experience psychological disorders in the form of anxiety about infant mortality by utilizing spiritual sources which is dhikr therapy in order to form adaptive coping mechanisms. General description of the problem in this study regarding the effect of dhikr therapy on the level of anxiety about losing a baby in severe pre-eclampsia pregnant women in the need for help model.. The purpose of this study was to identify the level of anxiety of severe pre-eclampsia pregnant women about losing their babies given the need for help model. This research method uses a pre-experimental design in the form of one group pretest-posttest. The sampling technique applied was accidental sampling as many as 35 severe pre-eclampsia pregnant women at the Comprehensive Emergency Neonatal Obstetric Service (PONEK) RSUD Dr. Moewardi Surakarta. Research result obtained before being given the need for help model through dhikr therapy, all respondents experienced anxiety, while after being given the intervention there were 12 respondents who did not experience anxiety and others still experienced anxiety.